2020
DOI: 10.1080/22221751.2020.1752117
|View full text |Cite
|
Sign up to set email alerts
|

Multiple recombinant events in human T-cell Leukemia virus Type 1: complete sequences of recombinant African strains

Abstract: Africa is the largest endemic area for HTLV-1, with many molecular genotypes. We previously demonstrated that some strains from North Africa (a-NA clade) originated from a recombinant event between Senegalese and West African strains. A series of 52 new HTLV-1 strains from 13 North and West African countries were sequenced in the LTR region and/or a env gene fragment. Four samples from French Guyanese of African origin were also added. Furthermore, 7 complete sequences from different genotypes were characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Indeed, the junction corresponds to the first shift in RNA template of the reverse transcriptase. In Senegal and Ghana, we also identified another clade (a-G-rec) resulting from recombination between a-WA and a-Sen strains (132). In this clade, we identified two points of recombination, one at the U3/RU5 junction and the other in the env gene.…”
Section: Recombination Occurs In Htlv-1mentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, the junction corresponds to the first shift in RNA template of the reverse transcriptase. In Senegal and Ghana, we also identified another clade (a-G-rec) resulting from recombination between a-WA and a-Sen strains (132). In this clade, we identified two points of recombination, one at the U3/RU5 junction and the other in the env gene.…”
Section: Recombination Occurs In Htlv-1mentioning
confidence: 82%
“…We recently showed that the a-Sen clade arose from recombination between a-WA and a-NA strains (130). Furthermore, some strains present in Guinea and Ghana coalesce into a subgroup named a-G-rec, which also arose through recombination between a-WA and a-NA strains (see the next section for more details) (132). The size of the circles is proportional to the number of strains identified.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…In addition, although recombinant forms of HTLV-1 have been described only in some African strains ( 47 ), we could not exclude recombinant forms of HTLV-1 as well HTLV-2 in coinfected individuals, as well as pseudotyping of HIV and HTLV-1/2.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed opposite effects of HTLV-1 expression on ICAM-1 and LFA-1 , which interact between infected and uninfected cells to promote virological synapse formation (50; 72). Despite recent reports of possible recombination events in the evolutionary history of some HTLV-1 strains (73; 74), the presence of a single integrated provirus in the majority of infected cells (31) suggests HTLV-1 has mechanisms to restrict superinfection (75). The downregulation of LFA-1 during reactivation might reduce the likelihood of superinfection following an encounter between infected cells, although LFA-1 is expressed in infected cells before reactivation at a higher level than in uninfected cells.…”
Section: Discussionmentioning
confidence: 99%